A Scoping Review of Foci, Trends, and Gaps in Reviews of Tobacco Control Research. Issue 5 (2nd February 2019) - Halas, Gayle; Schultz, Annette S H; Rothney, Janet; Wener, Pamela; Holmqvist, Maxine; Cohen, Benita; Kosowan, Leanne; Enns, Jennifer E; Katz, Alan
Abstract: Introduction: The burden of disease associated with tobacco use has prompted a substantial increase in tobacco-related research, but the breadth of this literature has not been comprehensively examined. This review examines the nature of the research addressing the action areas in World Health Organization's Framework Convention on Tobacco Control (FCTC), the populations targeted and how equity-related concepts are integrated. Method: A scoping review of published reviews addressing tobacco control within the primary prevention domain. We searched PubMed, Scopus, Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, Educational Resources Information Centre, and PsycInfo from 2004 to 2018. Results: The scoping review of reviews offered a "birds-eye-view" of the tobacco control literature. Within the 681 reviews meeting inclusion criteria, there was a strong focus on smoking cessation targeting individuals; less attention has been given to product regulation, packaging, and labeling or sales to minors. Equity-related concepts were addressed in 167/681 (24.5%); few were focused on addressing inequity through structural and systemic root causes. Conclusion: This analysis of foci, trends, and gaps in the research pursuant to the FCTC illustrated the particular action areas and populations most frequently addressed in tobacco control research. Further research is needed to address: (1) underlying social influences, (2) particular action areas and with specific populations, and (3) sustained tobacco use through the influence of novel marketing and product innovations by tobacco industry. Implications: This scoping review of the breadth of tobacco control research reviews enables a better understanding of which action areas and target populations have been addressed in the research. Our findings alongside recommendations from other reviews suggest prioritizing further research to support policymaking and considering the role of the tobacco industry in circumventing tobacco control efforts. The large amount of research targeting individual cessation would suggest there is a need to move beyond a focus on individual choice and decontextualized behaviors. Also, given the majority of reviews that simply recognize or describe disparity, further research that integrates equity and targets various forms of social exclusion and discrimination is needed and may benefit from working in collaboration with communities where programs can be tailored to need and context.